Challenges in the Current Management of Hepatocellular Carcinoma - Jogi, Soumya; Varanasi, Radha; Bantu, Sravani S; Saduvala, Sudha; Manne, Ashish (International Journal of Innovative Research in Medical Science, 2021)
Management of hepatocellular carcinoma (HCC) is complicated. Barcelona Clinic Liver Cancer (BCLC) staging system is widely used in risk stratifying HCC. It is different from anatomic staging (TNM) used in other cancers and is based on the liver function (Child-Pugh Score) and performance status at diagnosis along with tumor characteristics like size/number of primary, vascular invasion, and distant metastasis. Guidelines proposed by various liver societies help the treating physician select first-line therapy, but there are many limitations to them. Lack of reliable biomarkers that give objective information to monitor the response other than alpha-fetoprotein or radiological response is hurting the management strategies. There are no ideal predictors for recurrence and residual microscopic disease, especially after locoregional therapy (LRT) like surgical resection, ablation, transarterial chemoembolization (TACE), transarterial radioembolization (TARE), and stereotactic radiation therapy (SBRT). Also, there is no convincing evidence to use adjunct therapy along with LRT in localized HCC. There is a need to identify the subset of HCC that would benefit from peri-procedural therapy. Recommendations for treating advanced HCC with macrovascular invasion is not uniform across the guidelines. Some propose LRT (TACE and/or TARE) or recommend systemic therapy only like tyrosine-kinase inhibitors (TKI) or Immune-checkpoint inhibitors (ICI). A considerable portion of patients have poor liver function (Child-Pugh Score C) at diagnosis. In this era of medicine, we should give them options other than supportive care, but unfortunately, it is the preferred option. This population needs special attention in trials. In current practice, there only 2-3 classes of drugs available like TKI, ICI, and vascular endothelial growth factor (VEGF) inhibitors. There is a need to explore more classes of liver-friendly drugs in treating HCC, and the enrolment of patients in clinical trials must be advised in the guidelines.